PENGARUH SUPERVISI AKADEMIK TERHADAP KUALITAS PEMBELAJARAN DI MADRASAH ALIYAH SYARIFUDDIN LUMAJANG - Halimatus Sa’diyah; Moh Anwar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of academic supervision on the quality of learning at Madrasah Aliyah Syarifuddin Lumajang. This research employs a quantitative approach with an associative correlational survey design involving 36 teachers as respondents. Data were collected through questionnaires and documentation, and then analyzed using SPSS version 27. The findings indicate that the implementation of academic supervision is in the high category, as is the quality of learning achieved by teachers. The regression test shows a t-value of 3.853, which is higher than the t-table value of 2.032, with a significance level of 0.000 < 0.05, confirming a positive and significant influence of academic supervision on learning quality. The coefficient of determination (30.4%) further demonstrates that academic supervision contributes to improving the learning quality at the madrasah.